Projekt reformy ochrony danych osobowych - czy rzeczywiście powstanie jednolity i spójny system? - Grzelak, Agnieszka (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2014)
In January 2014 two years passed since the European Commission presented a package of reforms of the system of personal data protection in the EU. Com‑ mission proposed to create, in its opinion, a uniform and consistent system across the EU. The idea of the paper is to answer the question whether the Commission’s proposal to adopt two separate acts (one as a general system, and the second for cooperation in criminal matters and police), should meet the proposed assumptions. In order to analyze that, first the treaty background is presented, then current legal status in the field of personal data in the EU, and finally a comparative analysis of the solutions of the two drafts. The analysis leads to the conclusion that there are serious concerns about the lack of consistency.